Effect of biofertilizers and vermicompost on physico-chemical properties of soil under wheat (Triticum aestivum) crop - AECHRA, SUSHILA; MEENA, R H; MEENA, S C; JAT, HEMRAJ; DOODHWAL, KIRAN; SHEKHAWAT, ABHITEJ SINGH; VERMA, ANIL KUMAR; JAT, LALI (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted at the Instructional farm, Rajasthan College of Agriculture, Udaipur for two years (2017–18 and 2018–19) during the winter (rabi) season. The experiments were arranged in a randomized block design (RBD) manner with 3 replications. The results showed that, seed inoculation with biofertilizers (Azotobacter + Phosphorus solubilizing bacteria + Potash mobilizing bacteria + Zinc solubilizing bacteria) improved physico-chemical properties of soil except bulk density, particle density, pH, EC and showed higher availability of nutrients over control plot. Whereas in case of vermicompost (VC), physical properties such as BD, PD, porosity, WHC and chemical properties like pH, EC, CEC, OC and available nutrients were found distinctly enhanced under 50% VC at sowing + 50% VC at tillering in post-harvest soil over control. However, 50% VC at sowing + 50% VC at tillering significantly reduced bulk density, particle density, pH and EC. Furthermore, both biofertilizers and split application of vermicompost also significantly improved the productivity of wheat. It is concluded that application of biofertilizers and vermicompost could reliably be used to improve soil physico-chemical properties of wheat cultivated soils.